In vitro assessment of seminal traits and fertility parameters in fresh semen of Sahiwal bulls - RAMCHANDRAN, N; VERMA, G S; GUPTA, A K; RAINA, V S; MOHANTY, T K; SINGH, M K (The Indian Journal of Animal Reproduction, 2023)
Eight Sahiwal bulls maintained at Artificial Breeding Complex, National Dairy Research Institute, Kamal, Haryana were u ed to evaluate the seminal attributes and fertility parameters from fresh semen samples. The overall least squares means f r various seminal traits and fertility parameters were reported. The effect of bull was significant (P<0.01%) on parameters hke volume, pro ressive motility, per cent motility and on velocity of average path (P<0.05). The positive and the significant (P<0.05)_corre at1ons amon s_t the s_eminal traits and their significant (P<0.05) association with the fertility parameters suggest !hat c ns1?erat1on of the fert1hty traits along with the seminal traits would be valuable for selecting bulls to be used for artificial msemmat1on programme.